Memórias de vida de estudantes idosas em uma sociedade grafocêntrica: da ausência de escolarização ao letramento - Garcia, Silvana (2020)
This research is linked to the Master's Program in Management and Educational Practices at Nove de Julho University and its object of analysis is the problem of the lack of schooling in childhood and the presence of written language in elderly students who attend a literacy class at a Center Integrated Education for Young and Adults (CIEJA). The main objective of this study was to analyze the relations that the graphocentric society produces by hierarchizing the subjects who dominate the codes of written culture and those who are ignored by it. As specific objectives it aimed to rescue the memories of students and the relationship between the lack of schooling during childhood and the knowledge related to writing and literacy in order to promote the construction of a narrative of oneself that values the knowledge constructed throughout life. The research starts from the history of three women who are over seventy years old and attend an Integrated Center for Young and Adult Education (CIEJA). The universe defined for the realization of the study was a CIEJA belonging to the Municipal Education Secretariat of São Paulo located on the periphery of the East Zone of the same municipality that serves young people from fifteen years of age in Elementary School I and II. The nature of the research is of a qualitative nature and was composed by the life narratives of three elderly women. The instruments used for the construction of the narratives were questionnaires and semi-structured interviews. To support the studies on schooling, literacy, graphocentrism, the studies of Tfouni (2006, 2013, 2010), Galvão and Di Pierro (2007), Street (2004), Freire (1992, 1989, 1985, 1963) Romão and Gadotti (2011). The results showed that even without the mastery of the written language, these women are worthy of praise because they found formulas to overcome the imposition and the hierarchy to which they were exposed since childhood and overcame, in their own way, the obstacles imposed by the society that centers their practices in written culture and demands the same postures indiscriminately, even without offering the necessary conditions for its development.